Media and the city : cosmopolitanism and difference - Georgiou, Myria, 1971- (Cambridge, UK : Polity Press, 2013)
With the majority of the world's population now living in cities, questions about the cultural and political trajectories of urban societies are increasingly urgent. Media and the City explores the global city as the site where these questions become most prominent. As a space of intense communication and difference, the global city forces us to think about the challenges of living in close proximity to each other. Do we really see, hear and understand our neighbours? This engaging book examines the contradictory realities of cosmopolitanization as these emerge in four interfaces: co.
Includes bibliographical references (pages 162-175) and index.
Keywords: Mass media -- Social aspects; Cities and towns; Cosmopolitanism